Shear stress‐associated acquired von Willebrand syndrome in patients with mitral regurgitation. (17th October 2014) - Blackshear, J. L.; Wysokinska, E. M.; Safford, R. E.; Thomas, C. S.; Shapiro, B. P.; Ung, S.; Stark, M. E.; Parikh, P.; Johns, G. S.; Chen, D.
Summary Background Mitral valve regurgitation is associated with an acquired hemostatic defect. Objective We sought to assess the prevalence and severity of acquired von Willebrand syndrome in patients with native valve mitral regurgitation (MR). Patients/Methods Fifty‐three patients were prospectively observed with bleeding questionnaires and laboratory tests when undergoing an echocardiographic assessment of MR. In patients referred for mitral valve surgery, testing was repeated postoperatively. Results Echocardiography identified 13 patients with mild MR, 14 with moderate MR, and 26 with severe MR. Among patients with mild, moderate or severe MR, loss of the highest molecular weight von Willebrand factor (VWF) multimers occurred in 8%, 64%, and 85%, respectively, median platelet function analyzer collagen ADP closure times (PFA‐CADPs) were 84 s (interquartile range [IQR] 73–96 s), 156 s (IQR 104–181 s), and 190 s (IQR 157–279 s), respectively, and the ratios of VWF latex activity to antigen were 0.92 (IQR 0.83–0.97), 0.85 (IQR 0.76–0.89), and 0.79 (IQR 0.75–0.82), respectively (all P < 0.001). Nine patients reported clinically significant bleeding, and seven had intestinal angiodysplasia and transfusion‐dependent gastrointestinal bleeding (Heyde syndrome), with the median number of transfusions required being 20 (IQR 10–33; range 4–50). In patients who underwent mitral valve repair (n = 13) or replacement (n = 7), all measures of VWF function reported above improved significantly. Conclusion The high‐shear environment of moderate to severe MR is sufficient to produce prevalent perturbations in VWF activity. Acquired von Willebrand syndrome may occur in this setting, and appears to be reversible with mitral valve surgery.